Using crisis communications planning as part of a sustainable agritourism operation - Stacey F. Stearns; Doolarie Singh-Knights (Frontiers in Sustainable Tourism)
Economic viability is a key factor to sustainability for agritourism operations. A variety of challenges, including issues and crises can hinder whether an operation is open, economically viable, and sustainable. A crisis communications plan can help address and minimize any negative business impacts from weather, climate, or inherent risk, therefore, helping maintain the operation's economic viability. Although many agritourism operators have experience responding to an issue or crisis, including the pandemic, many still lack communications plans, and while this is also a problem in other sectors, agritourism operations with plans have increased sustainability potential.